Effect of Traditional Chinese Medicine ointment and rubbing technique on motor function in patients with hemiplegia in recovery stage of stroke (中药膏摩在中风病恢复期偏瘫患者运动功能康复中的应用效果) - HU Zhe (胡哲); YANG Junhang (杨俊行); FU Jingna (付景娜); SONG Ying (宋颖); LIU Wenli (刘文丽) (Association of Integrative Nursing, 2021)
Objective To explore the rehabilitation effect of Traditional Chinese Medicine (TCM) ointment and rubbing technique on motor function in patients with hemiplegia in recovery stage of stroke. Methods Totally 60 patients with hemiplegia in recovery stage of stroke were randomly divided into observation group and control group, with 30 cases in each group. The observation group received TCM ointment and rubbing technique on the basis of routine treatment and care; while the control group only received routine treatment and care. After 2 weeks of intervention, the motor function and living ability were assessed and compared between two groups. Results After 2 weeks of intervention, the scores of motor function evaluation scale (MAS) and Barther Index (ADL) increased in both two groups, and scores in the observation group were significantly higher than those in the control groups , with a significant differnce (P＜0. 05) . Conclusion TCM ointment and rubbing technique can promote the recovery of motor function and quality of life in patients with hemiplegia after stroke. (目的 探讨中药膏摩在中风病恢复期偏瘫患者运动功能康复中的应用效果。方法 将60例中风病恢复期偏瘫患者随机分为观察组和对照组, 各30例。对照组给予常规干预, 观察组在对照组基础上实施中药膏摩干预。观察2组干预前后患侧肢体运动功能和生活能力。结果 干预后, 2组运动功能评估量表(MAS)、Barther指数量表(ADL)评分均升高, 且观察组MAS、ADL评分高于对照组评分, 差异具有统计学意义(P＜0. 05)。结论 应用中药膏摩方法可以促进中风偏瘫患者运动功能恢复, 提高其生活能力改善, 是有效的中医护理干预措施。)